Currículo na etapa do ensino médio: entre a estética e a estetização - Soares, Caroline dos Reis (Universidade do Vale do Rio dos Sinos, 2021)
While perceiving and investing to understand the current context of humanist formation and arts decrease on Brazilian basic school curricula, this work aims to analyze the aesthetic dimension in curricula documents for the Brazilian high school. For this purpose, the investigative materiality is three curricula documents, they are The National Curricula Parameters, the National Curricula Guides, and the Nacional Comum Curricula Base. Considering those documents, it asks how is the articulation between curriculum and aesthetic dimension on the Brazilian high school stage? To answer this question, the working concepts are curriculum, aesthetics and aestheticization. Through 67 excerpts from the three documents, it was elaborated three analytical groups, they are Aesthetic and Education, Aesthetic in the Languages Area, and Aesthetic for Social Welfare. The analyses point to a tendency to empty the sense of aesthetics, being replaced by a utilitarian version of sensitive and art, the aestheticization. It concludes that aesthetic formation in the curriculum of the Brazilian high school stage, which is related to ethics and art, is essential for young people to be able to develop the critical, reflective, and analytical thinking of events, as well as it is fundamental for the formation of the sensitivity, and from looking at the constitutive differences of culture and life with the other.
Keywords: Currículo; Estética; Estetização; Ensino médio brasileiro; Curriculum; Aesthetics; Aestheticization; Brazilian high school